The Influence of Quality of Pharmaceutical Installation Services on Satisfaction of BPJS Outboard Patients in General Hospital dr. GL Tobing Tanjung Morawa - Nurita Dolok Seribu; Juliandi Harahap; Darwin Syamsul (Science Midwifery, 2022)
Patient satisfaction in hospital pharmacy services to support the quality of life of outpatients. Data on BPJS outpatient visits in July 2018 decreased by 21.5% at dr. GL. Tobing in Tanjung Morawa. The waiting time for pharmaceutical services in taking drugs is > 60 m+minutes and even taking drugs can be two to three days, it is suspected that the quality of pharmaceutical services has not been effective in the Pharmacy Installation. The purpose of the study was to analyze the effect of the quality of pharmacy installation services on the satisfaction of BPJS outpatients at the dr. GL. Tobing Tanjung Morawa. This type of research is quantitative with an explanatory research approach. The sample is 100 BPJS outpatients. The research was conducted in November 2019 - February 2020 through the distribution of questionnaires. Data were analyzed by univariate, bivariate and multivariate using multiple logistic regression test at a significance level of 95%. The results showed that service quality had a significant effect on BPJS outpatient satisfaction on the dimensions of reliability (p = 0.019), responsiveness (p = 0.013), assurance (p = 0.026), direct evidence ( tangible) (p=0.006), and empathy (p=0.003). The chance of patient satisfaction related to the quality of good pharmaceutical services is 86.23%. The conclusion that the dimensions of pharmaceutical service quality consist of reliability, responsiveness, assurance, direct evidence and empathy affect BPJS outpatient satisfaction. The dominant empathy variable affects patient satisfaction. The dominant empathy dimension affects patient satisfaction. It is recommended that the hospital management plan the proposed addition of pharmacists, drug planning, the availability of online entertainment services in the form of Wireless Fidelity (Wifi), regular communication training to officers and complete the identity and cellphone number in the patient's medical record. .